Australian coal mining: Estimating technical change and resource rents in a translog cost function - Azzalini, Paul; Bloch, Harry; Haslehurst, Paula (Oceania Association for Energy Economics, 2007)
This paper estimates a translog cost function for the Australian coal industry from 1968/69 to 2004/05. We use a variable measuring the shift to open-pit mining to capture the impact of embodied technical change, while using a time trend to capture the impact of other technical change and changing resource rents. The cost function is estimated with Zellner's SUR procedure. The shift to open-cut mining is shown to be important in lowering cost during the 1970s and 1980s, but more recently cost reduction is captured by the time trend.